PEMBUATAN DAN PENGGUNAAN ALAT KONVERTER UNIVERSAL OSILOSKOP SEBAGAI PERALATAN KATAGORI 2 PADA PRAKTIKUM ELEKTRONIKA DAYA - I Wayan Lastera; I Putu Arsikaputra (Jurnal SPEKTRUM, 2020)
To display electric waveforms in power electronics practicum, the instrumentused is an oscilloscope. With the limited range of test voltages from oscilloscopes themeasurement results for the power electronics lab are not good enough. To improvethe results of practicum, one effort that can be done is by making an universalconverter oscilloscope tool. The potential of this universal converter tool can beidentified by using it in uncontrolled AC electricity testing, controlled AC electricitytesting, uncontrolled DC electricity testing and controlled DC electricity testing. The testdata obtained are tabulated and analyzed descriptively, in order to be able to see andbe able to infer the potential of the oscilloscope universal converter. The test resultsshow that the use of an oscilloscope universal converter able to improve themeasurement results for power electronics practicum, proven to be able to be used inAC and DC mains voltage either uncontrolled or controlled with normal waveformdisplay, so that it can be used as category 2 equipment in the power electronicspracticum, in order to add equipment to the laboratory.